Pelatihan Penyusunan Laporan Arus Kas pada Nagata Motor - Fahada, Nazli; Hutahean, Thomas Firdaus; Benget P, Jhon Lismart (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
Cash flow statements are crucial instruments for MSMEs to monitor liquidity and support strategic decision-making; however, Nagata Motor still faces obstacles due to manual, disorganized financial recording that is often intermingled with personal funds. This Community Service (PKM) aims to improve the competence of Nagata Motor's owner in preparing accountable cash flow statements in accordance with Financial Accounting Standards (SAK). The implementation methods included conceptual socialization, practical training using digital-based templates, and intensive mentoring for one month. The results of the activity showed a significant increase in the partner's understanding of classifying cash flows into operating, investing, and financing activities. Post-training evaluation proved that the partner is capable of independently preparing accurate cash flow statements, which resulted in financial transparency and strengthened internal business controls. In conclusion, this training has successfully transformed Nagata Motor's financial management into a more professional system, prepared for future business expansion challenges.